THE TRANSFORMATION OF THE FINANCIAL REPORTING CONCEPT UNDER THE INFLUENCE OF DIGITAL TECHNOLOGIES (World Bulletin of Social Sciences, 2026)
In the context of rapid digitalization of the global economy, the traditional concept of financial reporting is undergoing significant transformation. This article examines the impact of digital technologies—such as artificial intelligence, big data analytics, blockchain, and cloud computing—on the conceptual foundations, structure, and quality characteristics of financial reporting. The study analyzes how digital tools reshape the processes of data collection, processing, disclosure, and interpretation of financial information. The findings demonstrate that digital technologies enhance transparency, reliability, timeliness, and decision-usefulness of financial reports, while also creating new methodological and regulatory challenges. The article concludes with recommendations aimed at improving the financial reporting framework in the digital economy